2021
DOI: 10.1155/2021/1182949
|View full text |Cite|
|
Sign up to set email alerts
|

The Effectiveness of Cochlear Implantation for Children of Hereditary Deafness: A Multicenter Retrospective Study

Abstract: Aim. To study the effectiveness of cochlear implantation in deaf children with gene mutation. Method. 420 children from three medical centers with cochlear implants were selected. Before wearing the cochlear implant and 6 months after wearing the cochlear implant, the children’s rehabilitation efficacy was evaluated through categories of auditory performance (CAP) and speech intelligibility rating (SIR). The SSF-MCDI and MUSS before and after the treatment were also compared. Results. The CAP and SIR scores of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…According to Liu et al, the earlier a child receives cochlear implantation, the better their hearing and speech abilities. 19 The age distribution of SIR scores also significantly varied from 1 to 6. (P=0.003).…”
Section: Discussionmentioning
confidence: 99%
“…According to Liu et al, the earlier a child receives cochlear implantation, the better their hearing and speech abilities. 19 The age distribution of SIR scores also significantly varied from 1 to 6. (P=0.003).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%